ANALISIS PROGRAM IMPLEMENTASI GERAKAN LITERASI SEKOLAH (GLS) DENGAN PENDEKATAN GOAL-BASED EVALUATION - Agus Widayoko; Supriyono Koes H; Muhardjito Muhardjito (Universitas Islam Negeri (UIN) Mataram, 2018)
Literacy skills are one of the basic skills of the 21st century. These skills become the basis of other skills, such as the ability to understand information analytically, critically, and reflectively. The School Literacy Movement (GLS) is one of the government's efforts to improve students' literacy skills. One of the programs is reading habituation 15 minutes before learning. The purpose of this research is to know the implementation of GLS program in schools, obstacles, and feedback related to improvement of GLS program implementation. This research uses evaluation method of Goal-Based Evaluation in analyzing GLS program. Respondents from this study are all school communities consisting of principals, teachers, employees, and students all over Indonesia who are willing to fill in google-form which contains questionnaires related to the implementation of GLS. The results of the evaluation indicate that 81.6% said that the GLS program has been implemented in the respondent's school, the reading habituation of 15 minutes in the school is in accordance with the national objectives, and 100% of respondents suggested that this activity should be continued with various inputs.